2000
DOI: 10.2214/ajr.174.1.1740213
|View full text |Cite
|
Sign up to set email alerts
|

Sonographically Guided Ethanol Sclerotherapy for Benign Thyroid Cysts

Abstract: Sonographically guided ethanol sclerotherapy is a safe and effective tool for the therapy of benign thyroid cysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
75
1
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(82 citation statements)
references
References 24 publications
4
75
1
2
Order By: Relevance
“…The numbers of PEI procedures were not different in both subgroups. Cho et al reported no difference in VRRs between pure and complex cysts 5 . For cysts containing thick, viscous fluid, two-step ethanol ablation may be used.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…The numbers of PEI procedures were not different in both subgroups. Cho et al reported no difference in VRRs between pure and complex cysts 5 . For cysts containing thick, viscous fluid, two-step ethanol ablation may be used.…”
Section: Discussionmentioning
confidence: 95%
“…In our group, the non-aspiration approach was used more frequently, both because less ethanol was applied and because the procedure was shorter and another injection was not needed to aspirate ethanol. The reported success rates range from 68% in a study by Cho et al to 100% in a study by Sung et al 5,15 . In our group, the success rates were identical for both small and medium-sized cysts.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…2 In patients with cosmetic or symptomatic problems, the initial procedure is the simple aspiration of the cystic portion; this reduces the cyst volume and aids in specific diagnosis, but it is associated with a high recurrence rate of up to 80%. 3,4 For recurrent cases after aspiration, ethanol ablation (EA) has been attempted with good results. 5,6 Recently, radiofrequency (RF) ablation has been used to treat benign thyroid nodules with a low complication rate, [7][8][9][10][11][12] including thyroid nodules with a cystic portion 6,8 and recurrent thyroid cancers.…”
mentioning
confidence: 99%